Hubungan Antara Lama Duduk Pengemudi Bis Terhadap Risiko Terjadinya Kondisi Neckpain - Permana, Agil Indra; , Arif Pristianto, SSt.FT.,M.Fis (2017)
Neckpain is closely related to the job of the driver. Because the daily activities are spent in a sitting position in static conditions and movements that are monotonous and always required concentration in controlling the vehicle. The condition causes fatigue and the neck muscles become tense, causing blood flow to the neck muscles that carry oxygen into obstructed and oxygen deficient muscles resulting in pain in the neck area. Objective: To determine the relationship between the long duration bus driver's seat while driving to the risk of neckpain conditions. Methods: This study is non experimental quantitative research with cross sectional design approach, which is used to identify the link between sitting time factor neckpainincident on bus drivers in Bus Station Tirtonadi Solo. Samples in this study a number of 81 samples, samples of research that all bus drivers who met the inclusion criteria. Results: In this study, bivariate analysis method used is the analysis of Chi SquareTest. From the analysis of Chi SquareTest test with a significance level of p = 0.000 shown smaller than the standard value of 0.05 (p <α). Thus, it means there is a significant relationship between prolonged sitting while driving to the condition of the occurrence of neckpain. Conclusion: Each time when driving was associated with the incidence neckpain. Keywords: Neckpain, Long Sitting, Bus driver